Catholic guilt? Recall of confession promotes prosocial behavior - McKay, Ryan; Herold, Jenna; Whitehouse, Harvey (2013)
Recent studies indicate that prosocial behavior is more likely when one feels guilty or when one's moral ledger has a negative balance. In light of such studies, we wondered whether religious rituals of atonement and absolution are, from the perspective of religious groups, counterproductive mechanisms for addressing the moral transgressions of group members. If sin is a form of capital, might absolution rituals squander that capital? We found that Catholic participants who recalled committing a past sin and being absolved of it donated significantly more money to the church than those who recalled committing the sin but had not yet recalled being absolved of it. This effect was more pronounced the more participants believed in divine judgment and the more they engaged in religious activities such as reading the bible or praying. Our findings indicate that the Catholic ritual of confession is an effective means of promoting commitment to the church. These results complement a cultural evolutionary approach to religious prosociality, whereby religious practices evolve to the extent they contribute to high levels of cooperation in religious groups.
Keywords: Catholic confession; absolution rituals; Cooperation; Cultural Evolution; Guilt; Morality; Prosocial behavior; Religion